Use of Electrochemical Peroxidation to Degrade Reactive Blue 19: Application of a 23 Full Factorial Design - Austero, Sheila B.; De Luna, Mark Daniel G. (ASEAN Journal of Chemical Engineering, 2011)
A 5000 g/m3 CI Reactive Blue 19 dye solution was treated using electrochemical peroxidation (ECP) process. This method involves the utilization of Fenton’s reaction chemistry through the addition of hydrogen peroxide into the solution and the use of an iron anode as source of Fe(II) catalyst. The degradation of the dye was evaluated using a 23 full factorial design augmented with four centerpoints. The factors and levels of the experimental design were as follows: initial pH (2.2, 2.5, 2.8), initial H2O2 dosage (332 mol/m3, 377 mol/m3, 422 mol/m3), and current density (164 A/m2, 205 A/m2, 246 A/m2). Results of the study showed that initial pH-current density interaction significantly influenced the percent COD removal. Moreover, after 60 minutes of treatment, the percent absorbance reduction reached up to 99.98% and the percent COD removal reached up to 82.83%.